The Roles of the Indonesian Constitutional Court in Determining State-Religion Relations - Muchamad Ali Safa'at (The Constitutional Court of the Republic of Indonesia, 2022)
Indonesia is neither a religious state nor a secular state. Based on the Pancasila state ideology and the 1945 Constitution, Indonesia adheres to a symbiotic model in which the state and religion are different entities but have a mutually influencing relationship. This relationship pattern can be seen from several laws that regulate issues related to religion, especially Islam, which is embraced by the majority of Indonesians. As a political product, the pattern of relations between the state and religion in the law is dynamic. However, in accordance with the principles of a democratic rule of law, the dynamics of democratic politics are controlled by legal instruments, one of which is through the authority to review laws as one of the powers of the Constitutional Court. The Constitutional Court’s decisions in cases of judicial review of laws related to religion reinforce the model of the symbiotic relationship between the state and religion. Such decisions affirmed Pancasila as a model of Indonesian secularity that is needed for the sake of individual rights and freedoms, to balance or reconcile religious diversity, social integration and national development, and the independent development of the functional domains of society.